Anthropologie médicale et socio-anthropologie des actions publiques - Jean-Pierre Olivier de Sardan (Anthropologie & Santé)
Health policies represent a specific kind of public policies. In the same way, anthropology of health can be considered in many respects as falling within socio-anthropology of public policies. It deals with the same issues of relationships between policy-makers and researchers. The issues of choice and relevancy of research themes can be solved in manifold ways: collaboration with policy-makers or public health specialists allows to renew research focus, while including sponsors as research objects. The issue of sponsors pressurizing problematics and methods requires them to acknowledge qualitative approaches’ specificities. The problem of applying research results is more complex: in order that resulting knowledge contributes to reforming actions, it seems necessary that research focuses more precisely on the very actors of public policies and the implementation of these policies in the field. Even then the institutions should accept results of the research in order to reform their own patterns of action. The exploratory concept of “practical norms” produces relevant knowledge that could help them doing so.